2005
DOI: 10.1007/s00467-005-1996-4
|View full text |Cite
|
Sign up to set email alerts
|

Colonic stricture secondary to hemolytic uremic syndrome caused by Escherichia coli O-157

Abstract: Shiga toxin-producing Escherichia coli (E. coli) is known to be one of the main causes of hemolytic uremic syndrome (HUS). Of the secondary complications of HUS, colonic stricture is relatively rare. We herein report on a Japanese girl that demonstrated sigmoid colon stricture secondary to HUS caused by an infection of E. coli O-157. Severe HUS occurred after the E. coli O-157 infection, so hemodialysis was performed due to renal failure. However, 1 month after recovery from HUS, abdominal symptoms occurred. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Late-onset strictures additionally show scarring and adhesion formation. These late-onset findings, still unclear in etiology, are thought to be a result of continued chronic inflammatory changes in the bowel itself [2,5]. The additional abnormalities of small bowel function found in this patient have not been previously described.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Late-onset strictures additionally show scarring and adhesion formation. These late-onset findings, still unclear in etiology, are thought to be a result of continued chronic inflammatory changes in the bowel itself [2,5]. The additional abnormalities of small bowel function found in this patient have not been previously described.…”
Section: Discussionmentioning
confidence: 77%
“…Seventeen cases of colonic stricture formation have been reported, including the current case [2]. Prior to this case, the longest reported interval between the acute phase of the illness and the onset of colonic stricture was 5 years [2]. There have been no reports of ongoing gastrointestinal complications or dysfunction following successful stricture resection.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Loirat et al [13] reported 1 % of cases in whom gastrointestinal complications required surgery, and in his study, Bernard et al [3] reported 5%: one case of colonic necrosis and one with intestinal intussusception. One case of colonic stricture post HUS was also described [17]. Colonic stenosis is a known complication of severe colitis [4,15].…”
mentioning
confidence: 97%